Hyaluronic acid-coated chitosan nanoparticles induce ROS-mediated tumor cell apoptosis and enhance antitumor efficiency by targeted drug delivery via CD44 - Wang, Tao (J Nanobiotechnology, 2017)
BACKGROUND: A targeted drug nanoparticle (NP) delivery system has shown potential as a possible cancer treatment. Given its merits, such as its selective distribution at tumor sites and its controllable drug release, drug-loaded NPs can be effectively delivered to selected organs and targeted cells, thus enhancing its antitumor efficiency and reducing its toxicity. METHODS: We reported that hyaluronic acid (HA)-coated chitosan NPs promoted the drug delivery of 5-fluorouracil (5-Fu) into tumor cells that highly expressed CD44. RESULTS: Our new findings suggested that HA-coated chitosan NPs enhanced drug accumulation by effectively transporting NPs into CD44-overexpressed tumor cells, and they also resulted in mitochondrial damage induced by the production of reactive oxygen species (ROS). Compared to free drug and uncoated NPs, HA-coated chitosan NPs exhibited stronger inhibition rates and induced obvious apoptosis in CD44-overexpressed A549 cells. CONCLUSIONS: Biocompatible and biodegradable HA-coated chitosan NPs were developed to encapsulate a chemotherapeutic drug (5-Fu) to enhance drug accumulation in tumor cells and to improve the agent’s antitumor efficiency by offering targeted drug delivery via CD44.